2022
DOI: 10.1002/chem.202200531
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Reactivity of B‐Connected Carboranylphosphines in Frustrated Lewis Pair Chemistry: A New Frame for a Classic System

Abstract: The primary phosphines MesPH 2 and tBuPH 2 react with 9-iodo-m-carborane yielding B9-connected secondary carboranylphosphines 1,7-H 2 C 2 B 10 H 9 -9-PHR (R = 2,4,6-Me 3 C 6 H 2 (Mes; 1 a), tBu (1 b)). Addition of tris(pentafluorophenyl)borane (BCF) to 1 a, b resulted in the zwitterionic compounds 1,7-H 2 C 2 B 10 H 9 -9-PHR(p-C 6 F 4 )BF(C 6 F 5 ) 2 (2 a, b) through nucleophilic para substitution of a C 6 F 5 ring followed by fluoride transfer to boron. Further reaction with Me 2 SiHCl prompted a HÀ F exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…Despite the long history of molecular H 2 activation by FLP, this chemistry remains the prospective field of research, as demonstrated in the recent perspective article by Stephan . Due to the high potential for practical applications, search for novel catalytic systems for hydrogen activation based on group 13–15 element compounds with tunable properties continues …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the long history of molecular H 2 activation by FLP, this chemistry remains the prospective field of research, as demonstrated in the recent perspective article by Stephan . Due to the high potential for practical applications, search for novel catalytic systems for hydrogen activation based on group 13–15 element compounds with tunable properties continues …”
Section: Introductionmentioning
confidence: 99%
“… 8 Due to the high potential for practical applications, search for novel catalytic systems for hydrogen activation based on group 13–15 element compounds with tunable properties continues. 9 …”
Section: Introductionmentioning
confidence: 99%